The Value chain Analysis at rattan Industry Cluster in south Lampung - Evi Yuniarti (Politeknik Negeri Lampung, 2014)
The objective of this research is to make deep analysis of how the rattan industry cluster manages activities within its firm value chain. This is important because through value chain analysis, the activities that have and have not contribute value added to firm’s competitive advantage can be identified. The analysis used include the analysis of the internal condition was done in two ways, Resources Analysis and Capability Analysis. The next step was done to assess the value chain analysis of five primary activities and four support activities. The results showed the rattan industry cluster has several strengths that are distinctive competencies which include economies of scale, strong marketing and service excellence. Besides weaknesses is the limited space in the factory warehouse, workplace less representative, the number of quality control is still not good for the parts of steam, weaving and finishing, coordination is still lacking, yet it has its own trademark (patent), as well as employee performance still relatively low perceived.Keywords: rattan industry cluster, value chain, distinctive competencies